A risk score to predict kidney survival in patients with autosomal recessive polycystic kidney disease at the age of two months - Burgmaier, Kathrin; Kilian, Samuel; Arbeiter, Klaus; Atmis, Bahriye; Boyer, Olivia; Buescher, Anja; Dursun, Ismail; Erger, Florian; Fila, Marc; Galiano, Matthias; Gokce, Ibrahim; Haeffner, Karsten; et al. (Kidney international, 2025)
Autosomal recessive polycystic kidney disease (ARPKD) is a severe hepatorenal fibrocystic disorder. Its rareness and the variability of disease courses have been major obstacles for the establishment of clinical trials on treatment of kidney disease in ARPKD. In this observational study we characterized kidney disease progression in a very large cohort of up to 658 patients with the clinical diagnosis of ARPKD and identified risk factors associated with rapid kidney disease progression. The estimated probability of kidney failure by the age of 20 years was 50.1% (95% confidence interval 42.2%‒57.0%), with earlier kidney failure in specific subgroups. Mean yearly estimated glomerular filtration rate decline after the first year of life was 1.3 ml/min per 1.73 m2 during childhood and adolescence in the overall cohort, ranging from 0.5 to 2.2 ml/min per 1.73 m2 in various subgroups. Furthermore, we developed prediction models for the relative risk of early kidney failure to be applied at the age of two months in daily clinical life. The finally chosen predictor set for a score based on a Cox model encompassed five factors: gestational age at oligo- or anhydramnios, gestational age at birth, functional genotype, serum creatinine (mg/dl) as well as documentation of arterial hypertension at the age of two months. The derived simple prognostic score showed good prediction performance, especially in the first three years of life. It reliably identified patients who are not at risk of early kidney failure and may be helpful to identify patients at risk of more rapid disease progression that could benefit from novel therapeutic interventions.
Gesehen am 21.01.2025